DIGITAL TOURISM: HOW INDUSTRY 4.0 WILL AFFECT THE TOURIST INDUSTRY IN THE REGION - E. Y. Shchedrina; A. G. Moiseeva; A. N. Goncharov; V. V. Khubulova (Современная наука и инновации)
Prospects for the creation of a personalized information space of tourist resources, considered the basis for digital transformations in the field of tourism in the regional spectrum.